Novel D − π − A dye sensitizers of polymeric metal complexes based on 8‐hydroxyquinoline and phenylethyl or fluorene units: synthesis, characterization and photovoltaic applications for dye‐sensitized solar cells. (23rd July 2013) - Yu, Xiaoguang; Jin, Xueliang; Tang, Guipeng; Zhou, Jun; Zhang, Wei; Hu, Jiaomei; Xie, Qiufang; Zhong, Chaofan
Abstract : Four novel donor − π‐bridge − acceptor (D − π − A) polymeric metal complexes (P1–P4) based on 8‐hydroxyquinoline metal complexes were synthesized and tested for their performance in dye‐sensitizedsolar cells (DSSCs). The polymeric metal complexes dyes use alkoxy benzene or alkyl fluorene as the electron donor and C=C as π linker; the 8‐hydroxyquinoline derivative complex part was used as the electron acceptor and diaminomaleonitrile was used as ancillary ligand. The two strongly electron‐withdrawing cyano groups in the polymer structure can provide an efficientcharge transport in theintramolecular between donor and acceptor parts. The thermal, photophysical, electrochemical and photovoltaic properties of these copolymers were investigated by TGA, differential scanning calorimetry, cyclic voltammetry and cureent density‐voltage curves, and the results showed that dye containing complex Zn(II) and alkoxy benzene unit benefited the generation of photocurrent and open‐circuit voltages, and a maximum power conversion efficiency of 1.91% (P2) was obtained, with an open‐circuit voltage of 0.71 V, a short‐circuit current density of 4.23 mA cm −2, and a fill factor of 38.6% under AM1.5G irradiation. The study results also show that the four polymers exhibit goodthermal stability, indicating that these polymeric metal complexes are suitable for the fabrication processes of optoelectronic devices. Copyright © 2013 John Wiley & Sons, Ltd. Abstract : In this article, four novel D‐π‐A structure polymeric metal complexes (P1, P2, P3, P4 ) with were synthesized, in which 8‐HQ derivative complex part was used as the electron acceptor, C = C were used as π‐bridge, and alkoxy benzene or alkyl fluorene was used as the electron donor. the results showed that dye containing complex Zn(II) and alkoxy benzene unit benefited the generation of photocurrent andthe open circuit voltages, and the maximum power conversion efficiency(PCE) of 1.91% (P2) was obtained.